The Trouble With Corporate Compliance Programs - Haugh, Todd; Gillespie, Nicole; Ferrin, Donald; Hurley, Robert; Kramer, Roderick; Tyler, Tom; Griffith, Sean; Dienhart, John; Wasieleski, David; Stucke, Maurice (MIT Sloan Management Review, 2017)
Multinational corporations spend millions of dollars per year on compliance. In highly regulated industries, such as health care and finance, large companies spend much more, sometimes hiring hundreds or even thousands of compliance officers at a time. There is often a belief on the part of corporate leaders that when rigorous compliance programs are in place, employee wrongdoing will largely disappear. If something does go wrong, the hope is that having a comprehensive program will help convince regulators that the company's compliance initiatives were "effective," the standard used in U.S. sentencing guidelines. Unfortunately, even today's most comprehensive programs won't curtail corporate wrongdoing or the government intervention that follows. Volkswagen AG's compliance program didn't stop its employees from installing "defeat device" software to cheat emissions tests, nor did Wells Fargo & Co.'s policies prevent its employees from opening new customer accounts without authorization. More than 15 years after the Enron Corp. scandal, most companies know very little about how employees make ethical decisions or the psychological mechanisms that cause them to perform unethical and illegal acts. Even fewer have compliance strategies aimed at curbing such behaviors. The goal of this article is to pull together the burgeoning field of behavioral ethics, which provides insight into how individuals make ethical decisions, with the work of criminologists who study individual and corporate criminality. The author seeks to explain why corporate compliance efforts are falling short and how those efforts can be improved. In addition, he offers practical and cost-effective strategies for improving compliance programs that focus on employee behavior, which he says is the best way to make compliance truly effective. Corporate compliance depends on the behavior of individual employees. If employees, officers, and managers always acted in a law-abiding and ethical manner, compliance failures would rarely occur. But that is not realistic. That is why companies need to be aware of how and why employees act the way they do. This starts with understanding how people make decisions generally and how that translates to ethical decision-making. The article describes eight common rationalizations used by those committing unethical and illegal acts within companies. Corporate leaders need to understand these rationalizations and be able to identify their usage as ...